Coercive or supportive: an assessment of NGOs role in sustainable supply chains adoption - Nezakati, Hossein *; Fereidouni, Meghdad Abbasian; Bojei, Jamil; Ho, Jo Ann (Econjournals, 2016)
On one hand businesses can be criticized by non-governmental organization (NGOs) scrutiny, on the other hand companies can be supported from NGOs to remove the barriers and positively influence on customer perceptions. The aim of this study is to critically assess the role of NGOs in sustainability two different perspectives, namely, “coercive view” and “supportive view.” This study may benefit the NGOs partnering with Multination Companies (MNCs) to identify the effect of this partnership on small and medium enterprises (SMEs). Also, SMEs and MNCs can use the framework to mind more the role of NGOs in their SSCM. Using literatures support, This Study found that, NGOs support MNCs can lead to MNCs reputation and empowering, whereas this relationship make some barrier in SMEs’ sustainability practice by increasing costs of new market entry. Moreover, SMEs can use NGOs support to remove adoption barriers and increase their profits.